OPTIMALISASI DIGITAL MARKETING DALAM MENINGKATKAN MINAT SANTRI DI LEMBAGA PENDIDIKAN AL-QUR’AN - Rahmia; Akhmad Shunhaji; Farizal MS (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to analyze the optimization of digital marketing in increasing students’ interest in Qur’anic educational institutions. This research employs a qualitative approach with a field research design, where data were collected through observation, in-depth interviews, and documentation involving institutional managers, teachers, students, and parents. Data were analyzed descriptively through data reduction, data display, and conclusion drawing. The findings reveal that the utilization of digital marketing through social media platforms such as WhatsApp, Instagram, and Facebook significantly enhances students’ interest, as indicated by increased engagement, inquiries, and enrollment of prospective students. Religious and emotionally driven content is found to be more effective in attracting attention and building public trust. However, the optimization remains constrained by limited human resources and the absence of a systematic digital marketing strategy. Therefore, a more structured and sustainable digital marketing management is required to improve the competitiveness of Islamic educational institutions in the digital era.